2013
DOI: 10.1093/gji/ggt124
|View full text |Cite
|
Sign up to set email alerts
|

Automating seismic waveform analysis for full 3-D waveform inversions

Abstract: We present a semi-automatic seismic waveform selection algorithm that can be used in full 3-D waveform inversions for earthquake source parameters and/or earth structure models. The algorithm is applied on pairs of observed and synthetic seismograms. A pair of observed and synthetic seismograms are first segmented in the wavelet domain into a number of wave packets using a topological watershed algorithm. A set of user-adjustable criteria based on waveform similarities is then applied to match each wave packet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…(2) 3-D background models are used to compute Fréchet derivatives, thereby accommodating nonlinearities due to structure; (3) data may be assimilated based on automated measurement window-selection algorithms (Maggi et al 2009;Lee & Chen 2013); (4) as a result of (1)-(3), the amount of usable data steadily increases from iteration to iteration, thus enabling the extraction of more information from seismograms, ultimately culminating in global 'full-waveform inversion ' (FWI), that is, the use of entire three-component seismograms; and (5) the crust and mantle are inverted jointly, thereby eliminating the need for crustal corrections. The goal of this study is to harness 3-D simulations of seismic wave propagation in combination with adjoint-state methods to image the crust and mantle.…”
mentioning
confidence: 99%
“…(2) 3-D background models are used to compute Fréchet derivatives, thereby accommodating nonlinearities due to structure; (3) data may be assimilated based on automated measurement window-selection algorithms (Maggi et al 2009;Lee & Chen 2013); (4) as a result of (1)-(3), the amount of usable data steadily increases from iteration to iteration, thus enabling the extraction of more information from seismograms, ultimately culminating in global 'full-waveform inversion ' (FWI), that is, the use of entire three-component seismograms; and (5) the crust and mantle are inverted jointly, thereby eliminating the need for crustal corrections. The goal of this study is to harness 3-D simulations of seismic wave propagation in combination with adjoint-state methods to image the crust and mantle.…”
mentioning
confidence: 99%
“…The choice of the misfit function is a key step that affects the success and the convergence of FWI (e.g., Modrak & Tromp, 2016). It is common to split seismic traces into smaller measurement windows using window‐selection algorithms (e.g., Chen et al., 2017; Lee & Chen, 2013; Maggi et al., 2009) to select high‐quality portions of seismograms and maximize the information extracted from each time series. Both time‐domain cross‐correlation (Dahlen et al., 2000; Luo & Schuster, 1991; Marquering et al., 1999; Tanimoto, 1995; Tromp et al., 2005) and frequency‐dependent multitaper cross‐correlation (Tape et al., 2009; Zhou et al., 2004, 2005) measurements tend to highlight the maximum amplitude signals in measurement windows where scattered waves, which provide valuable constraints on the structure of the medium they propagate through, are generally suppressed (e.g., Rickers et al., 2012).…”
Section: Adjoint Tomographymentioning
confidence: 99%
“…Nolet (1987) discussed the statistics of picking travel times in seismology when their probability distribution is away from Gaussian one. Using a data-driven strategy, Maggi et al (2009) had performed time window detection either on observed seismograms or on synthetic seismograms while Lee and Chen (2013) have developed a frequency-time window detection. We may consider data-driven strategies where only observed seismograms are analyzed (Chevrot, 2002;Gentili and Michelini, 2006;Rowe et al, 2002;Zhang et al, 2003) and model-driven strategies where observed seismograms are compared with synthetic ones computed in a reference model.…”
Section: Travel-time Estimation a Data Mining Issuementioning
confidence: 99%